Efficiency Of Variety Oven Tobacco Farming 88 In Jerowaru District, East Lombok District - Warni, Anggitia; Muhsin, Muhsin; Nirmawati, Nirmawati (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
This research can determine the amount of income received by farmers of variety 88 oven tobacco in Jerowaru Village, East Lombok Regency, on average Rp. ,36,257,950,- The amount of income received is proportional to the costs incurred in cultivating oven tobacco variety 88. Farming oven tobacco variety 88 in Jerowaru District, East Lombok Regency, the implementation of farming is relatively efficient, this is indicated by the R/ C Ratio value of 1 .9, in other words R/C > 1. means that cultivating tobacco varieties 88 in Jerowaru District is efficient or feasible to implement or continue. The obstacle faced in cultivating variety 88 oven tobacco is capital, because capital is one of the determining factors for success in carrying out variety 88 oven tobacco farming activities. Next, there is the obstacle of the availability of fertilizer which is relatively high in price, while the final obstacle is the recent uncertain weather factor. Finally, this has become a threat that causes tobacco farming harvests to fail, causing huge losses for tobacco farmers.